MODE OF PRESENTATION AND ROUTE OF DELIVERY IN TWIN PREGNANCY - Afra Rehman', Yasmeen Joyo2,Rozina Memon',Saira Parveen4,Mehnaz Akram Shaikh5, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2019)
Introduction Two things to know early are very significant in twin pregnancies. One is mode of presentation and other is to decide the mode of delivery as lack of knowledge in this context can jeopardize not only life of mother but also of baby. Before the development of this situation, it is better to know them early. Fetal presentation was considered to be the main modifier of the effect. The mode of delivery usually affects the CNS of neonate but consequences are still not known. Some authors indicate that there occurs effect on the function of Hippocampus. vertex-vertex is the commonest presentation and vaginal delivery is commonest route of delivery. Purpose of study: The aim is to know the mode of presentation and route of delivery in twin pregnancies. Material and methods:-The study was done in Department of Gyn/Obs Unit 2 at PMCH Nawabshah. This is a cross sectional study. Only pregnant ladies were selected for the study having the twin pregnancies diagnosed on ultrasound. Patients with single baby were excludd from the criterion. Results:-Total 120 patients were taken for the study. Out of them, 42 (359c) were found to have twin pregnancy. Mostly the patients were reported in 35-36 weeks. 35.7' o patients were found in this scenario. The common mode of presentation was vertex vertex among 12 (28.579c) patients. The common route of delivery in our study in first and secod twin was vaginal having 309c and 28' o respectively. Conclusion:- It is concluded that to find out mode of presentation of baby helped a lot to resolve the problem of route of delivery as it was already decided.